CONSIDERATIONS ABOUT ECONOMIC CRISIS IMPACT ON AGRO-FOOD PRODUCTS DEMAND IN ROMANIA - Raluca Andreea, Ion; Mirela, Stoian (Economics of Agriculture, 2011)
Consumption of food products has signifcant share in total consumption expenditure of a household in Romania. Therefore, how consumer demand for different products reacts according to their price changes and household income is important for food business managers in making decisions about increasing or reducing the prices for their output. In this paper the elasticity coeffcients of demand for agricultural products to price and income are measured and the way demand reacts in the context of economic crisis is identifed. The economic crisis may manifest as either by increasing prices or reducing real incomes. The results show that demand for food products respond differently to price and income changes: basic food have an inelastic demand and products with a high degree of processing, animal food in general, have elastic demand.